PEMBELAJARAN KETERAMPILAN BERBICARA DENGAN METODE DISKUSI DI SEKOLAH DASAR - Herlinda, Kiki; Mahdjuddin, Ritawati; Indrawati, Tin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
This research is motivated in elementary school that the learning activity is dominated by teacher, consequently the result of learning to speak student skill becomes low. The purpose of this study is to describe the plan, implementation and learning outcomes of students in improving speaking skills using the method of discussion. The result of research has increased, RPP observation of cycle I is 64,28% and in cycle II 82,14%. Teacher cycle I aspect is 72,5% to 87,5% in cycle II and on student aspect of cycle I is 62,5% to 80,0% in cycle II. Results of student learning with an average score of 69.02 in cycle I to 83.6 on cycle II. Thus, discussion methods can improve students' speaking skills. Keywords: Result of speaking skill, method of discussion